2000
DOI: 10.1038/sj.sc.3100931
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of 4-AP in chronic spinal cord injured subjects

Abstract: Study design: A prospective double blind cross over trial of intravenous 4-Aminopyridine (4-AP). Objective: To determine the ecacy of this drug in the treatment of spinal cord injured (SCI) patients for neurologic impairment, pain and spasticity. Setting: The post anesthesia care unit (PACU) of a tertiary care acute hospital. Methods: Twelve paraplegic patients were enrolled in a double blind cross over intravenous trial of 4-Aminopyridine (4-AP). Thirty milligrams of 4-AP or placebo were administered over a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…However, the medication duration could have been longer, as suggested by positive participant feedback. Past researchers have reported that carryover may last up to 48 h. 3,11,13 Currently, the optimum dosage and administration for 4-AP remains unclear. 33 A complete dose response curve has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the medication duration could have been longer, as suggested by positive participant feedback. Past researchers have reported that carryover may last up to 48 h. 3,11,13 Currently, the optimum dosage and administration for 4-AP remains unclear. 33 A complete dose response curve has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The 4-AP (Fampridine-SR) group revealed improved sensation and responded more positively to the drug efficacy and improved quality of life due to the medication. In a similarly designed crossover study, Donovan et al 13 investigated nonambulatory, chronic SCI subjects and found no evidence of superior gains in the group receiving 30 mg intravenous 4-AP on motor, sensory, spasticity and pain scores.…”
Section: Introductionmentioning
confidence: 99%
“…Peak concentrations of 121 and 162 ng/ml seen in two of the subjects were equivalent to peak plasma levels seen in previous studies of maximal tolerable systemic doses. 5 On the other hand, data from the intravenous portion of this study 13 indicate that the concentration expected in the CSF is only about 50% of that seen in the plasma, therefore the local concentrations achieved seem likely to be higher than those that have been produced with systemic administration. These local concentrations appeared to be su cient to produce localized increases in re¯ex responses to Figure 2 Concentration of 4-aminopyridine in the cerebrospinal¯uid taken from two subjects before, during, and after intrathecal infusion of 4-aminopyridine at a rate of 5 mg/h cutaneous stimulation, and even su cient to focal muscle fasciculation, but did not clearly lead to clinically useful improvements in function.…”
Section: Discussionmentioning
confidence: 67%
“…13 These patients had been recruited from a population of chronic spinal cord injury patients referred to The Institute for Rehabilitation and Research for their rehabilitation care including the management of problems related to pain and/or spasticity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation